An association of serum ALT with elevated blood pressure in senior adults: a case-control study. (16th November 2016) - Hong, Xiuqin; Wongtongkam, Nualnong; Ward, Paul Russell; Xiao, Shuiyuan; Wang, Shuling; Peng, Qian; Zuo, Qi; Zeng, Dan; Wang, Jia; Wang, Chenxu; Chen, Jian; Zhang, Na
ABSTRACT: Hypertension is a major risk factor for cardiovascular diseases in China; hence, identifying good serum markers might provide cost benefits in terms of reducing morbidity rates. In this population-based case-control study, participants were recruited from five districts in Hunan province, and 416 cases were matched with an equal number of controls. Markers related to elevated blood pressure were assessed: Body Mass Index, total cholesterol, triglycerides, fasting blood glucose, and creatinine. Three potential serum markers homocysteine (HCY), C-reactive protein (CRP), and alanine aminotransferase (ALT) were dichotomized as normal or high level. Binary logistic regression was used to determine odds ratios (ORs) and 95% confidence intervals (CIs). The findings showed that ALT is a powerful serum marker for predicting high risk of high blood pressure with OR = 2.94, 95% CI (1.44–6.02), while there were no significant differences between cases and controls for HCY and CRP. Additionally, it seems likely that high concentrations of HCY conferred a protective effect against elevated blood pressure. When adjusted for sex, ORs for hypertensive females were nearly five times higher than for hypertensive males (OR = 4.34, 95% CI = 1.17–16.04). The study strongly supports findings showing ALT is a potential indicator for patients with hypertension.